Managerial Readiness of Early Childhood Education Institutions in Addressing the Climate Crisis: A Comparative Study Across Regions in Bandung, West Java - Dewi Mulyani; Asep Herry Hernawan; Laksmi Dewi (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This research is driven by the urgent need for managerial leadership in integrating climate change issues into Early Childhood Education (ECE) curricula, an effort often hindered by geographical disparities and resource accessibility. This study aims to analyze the managerial readiness of ECE principals in designing climate change curricula and to conduct a comparative study on the availability of environmental intelligence learning media between urban centers and suburban areas in Bandung. A descriptive-comparative quantitative method was employed, involving 45 ECE principals and administrators as respondents. Data were collected through validated questionnaires covering curriculum design dimensions and infrastructure availability. The findings reveal significant differences in managerial readiness and the availability of learning media between institutions in the urban center (Zone B) and suburban areas (Zone D). Principals in the urban center demonstrated higher scores in curriculum formalization and access to digital media, whereas suburban institutions relied more heavily on nature-based media but remained administratively underdeveloped. Nevertheless, both regions showed a strong alignment in their views regarding the integration of environmental theology as a foundational element of the curriculum. This study concludes by emphasizing the importance of managerial standardization and the equitable distribution of learning media to bridge the climate literacy gap across different regions in Bandung.